TINJAUAN YURIDIS PENEGAKAN HUKUM TERHADAP KAPAL PERIKANAN ASING YANG MELAKUKAN ILLEGAL FISHING DI PERAIRAN ALUR LAUT KEPULAUAN INDONESIA DALAM PERSPEKTIFHUKUM LAUT INTERNASIONAL - Hasugian, Dohardo Maharari; Lestari, Maria Maya; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The large potential of fishery resources in Indonesian territorial waters is no longer a secret between countries, proper management is an advantage for the domestic economy, including cooperation with other countries in fisheries management in the form of an agreement. UNCLOS 1982 became a new breakthrough in fisheries potential as well as the fruit of Indonesia's struggle to solidify the concept of an archipelagic country since the djuanda declaration. However, it turns out that the facts in the field say that Indonesia often has its fishery wealth stolen by foreign fishing vessels in various modes, not forgetting that the sea lanes of the Indonesian archipelago are used as objects for illegal fishing or places of flight, considering that other countries are given the right to cross archipelagic countries which are regulated in national law and guaranteed. by international law. The importance of law enforcement against such theft or what is commonly called illegal fishing is imperative to prevent the same violations and protect Indonesia's fishery wealth.This type of research is a normative legal research that is using literature study in finding data. This research is descriptive in nature which tries to provide detailed and detailed data on the existing problems. In writing this research using qualitative data analysis which means explaining and concluding about the data that has been collected by the author. This study uses secondary data or scientific data that has been codified.The results of this study are to explain the relationship between international law and national law in handling illegal fishing in the sea lanes of the Indonesian archipelago. Of which there are still a number of provisions that need to be regulated, especially regarding law enforcement, so it is necessary to make a regulation related to this matter which can later become a legal basis for enforcing fishing theft and protecting the wealth of Indonesia's fishery resources.Keywords:Law Enforcement, Illegal Fishing, Indonesia Archipelagic Sea Lanes